2020
DOI: 10.2196/21419
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions and Attitudes Toward COVID-19 Nonpharmaceutical Interventions Across Six Countries: A Topic Modeling Analysis of Twitter Data

Abstract: Background Nonpharmaceutical interventions (NPIs) (such as wearing masks and social distancing) have been implemented by governments around the world to slow the spread of COVID-19. To promote public adherence to these regimes, governments need to understand the public perceptions and attitudes toward NPI regimes and the factors that influence them. Twitter data offer a means to capture these insights. Objective The objective of this study is to identify tweets about CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 24 publications
1
105
0
2
Order By: Relevance
“… 32 Further, seven papers reported international samples. 23 , 33–38 With the exception of one study that only reported 777 869 Twitter ‘tweets’, 37 the mean number of participants in each study was 5293 (standard deviation = 9105), with median number of 1625 participants (range = 482–37 077). Most studies used cross-sectional survey designs ( k = 22), whereas other design types included longitudinal surveys ( k = 3), 14 , 23 , 38 quasi-experimental ( k = 1), 17 experimental designs ( k = 2) 21 , 32 and media analysis ( k = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 Further, seven papers reported international samples. 23 , 33–38 With the exception of one study that only reported 777 869 Twitter ‘tweets’, 37 the mean number of participants in each study was 5293 (standard deviation = 9105), with median number of 1625 participants (range = 482–37 077). Most studies used cross-sectional survey designs ( k = 22), whereas other design types included longitudinal surveys ( k = 3), 14 , 23 , 38 quasi-experimental ( k = 1), 17 experimental designs ( k = 2) 21 , 32 and media analysis ( k = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used cross-sectional survey designs ( k = 22), whereas other design types included longitudinal surveys ( k = 3), 14 , 23 , 38 quasi-experimental ( k = 1), 17 experimental designs ( k = 2) 21 , 32 and media analysis ( k = 1). 37 Convenience sampling methods were used in almost all included studies ( k = 14 convenience samples and k = 13 stratified convenience samples), with the exception of two studies that relied on random sampling 14 and quota sampling 34 methods. About one-third of the included studies ( k = 11) were preprints 10 , 12 , 13 , 15 , 21 , 23 , 28 , 32 , 33 , 36 , 38 and one study was a report by an organization (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to efforts from all sectors of society, high adherence to the lifestyle modifications suggested by the government and public health organizations greatly delayed the spread of the disease [ 47 ]. In our findings, 64.6%-86.6% of respondents reported practicing five major preventive behaviors more frequently in the preceding week.…”
Section: Discussionmentioning
confidence: 99%
“…preventive measures, such as lockdown, closure of non-essential establishments and businesses were successfully respected, in other countries these measures were not or partially accepted (Doogan et al, 2020). Other papers have shown several negative psychological eects of social isolation of COVID-19 patients, such as high levels of anxiety, stress, or even the presence of depressive symptoms that can persist after the pandemic (Antunes et al, 2020;Duan et al, 10 2020).…”
Section: Social and Cultural Analysesmentioning
confidence: 99%